IMPROVING THE COMPETITIVENESS OF THE REGION: CLUSTER APPROACH - A. Kamalova (Publishing House of the State University of Management, 2016)
The article covers some conceptual approaches and best practices of implementing the cluster polices in practice to stimulate success and competitiveness.